Analisis Manajemen Risiko Sistem Informasi KKN Universitas Lamung - noviyanti noviyanti; Aristoteles Aristoteles; Yunda Heningtyas; Tristiyanto Tristiyanto (Jurusan Ilmu Komputer Fakultas MIPA Universitas Lampung, 2018)
KKN is an intracurricular activity that provides learning and work experience to students in community development activities. The Implementation Board of the Real Work Program (BP-KKN) of the University of Lampung made the information system an important component in the implementation of KKN. BP-KKN's success in carrying out its duties depends on the extent to which the KKN information system management has been implemented. The use of the KKN information system raises various risks that can interfere with the implementation of KKN and cause losses both non-material and material to BP-KKN. BP-KKN needs to apply risk management to reduce the risks that arise, so that the problems caused do not result in the use of KKN information systems being hampered. The method used is NIST 800-30 which is an information system risk management framework with three stages, namely risk assessment, risk mitigation, and risk evaluation. KKN has 9 risks that can interfere with the sustainability of the information system. The final result of the KKN information system risk management is in the form of recommendations given to reduce the risk that will occur in the information system.